2004
DOI: 10.1111/j.0141-9889.2004.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Irish Catholic ill health in Scotland: a qualitative exploration of some links between ‘religion’, class and health

Abstract: This paper considers the ways in which accounts from GlasgowCatholics diverge from those of Protestants and explores the reasons why people leave jobs, including health grounds. Accounts reveal experiences distinctive to Catholics, of health-threatening stress, obstacles to career progression within (mainly) private-sector organisations, and interactional difficulties which create particular problems for (mainly) middle class men. This narrows the employment options for upwardly mobile Catholics, who may then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Socio-economic position explained about half of the morbidity excess for middle-aged Catholics in Glasgow [ 27 ]. Some qualitative data have suggested that institutional sectarianism restricting employment opportunities for (especially older) Catholics may have been a cause of the higher mortality for this group [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Socio-economic position explained about half of the morbidity excess for middle-aged Catholics in Glasgow [ 27 ]. Some qualitative data have suggested that institutional sectarianism restricting employment opportunities for (especially older) Catholics may have been a cause of the higher mortality for this group [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The religious may ignore or ostracize those who do not belong to their church. Those not belonging to a dominant religion may face obstacles to obtaining resources, hardships, and stress that deleteriously affect their health (Bywaters et al 2003;Walls and Williams 2004). Religious leaders may abuse their own members physically, emotionally, or sexually (Rossetti 1995;Tieman 2002).…”
Section: The Negative Effects Of Religion On Healthmentioning
confidence: 99%
“…One explanation for this inequality is sectarian conflict which is most overt in relation to provision of Catholic schools and among fans of rival sports clubs (Bradley, 2006;Flint, 2012). More profoundly, lower socio-economic status and concomitant health problems among Scottish Catholics relative to Protestants have been attributed to discriminatory employment practices and latent sectarianism (Walls and Williams, 2003;Walls and Williams, 2004). Other authors dispute the importance of sectarianism in modern Scotland and suggestions that it contributes to the Scottish effect (excess mortality in Scotland in comparison with other regions of the UK that is not entirely explained by socio-economic status (SES) at either the individual or area level (Popham and Boyle, 2011)) have received little support (Graham et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In Scotland, although widespread violent conflict has been avoided, debate regarding the prevalence of sectarianism prompted the late introduction of religion questions to the 2001 Census. It has been suggested that prejudice against the minority Catholic population in the employment market has restricted upward social mobility, leading to higher levels of health problems associated with economic deprivation (Walls and Williams, 2004;Walls and Williams, 2003). Equality legislation of the type seen in Northern Ireland was not enacted in Scotland or the rest of Great Britain until the Equality Act of 2010 and there remains no analogue to the FETO.…”
Section: Introductionmentioning
confidence: 99%